Perception of Sustainable Fashion among millennials in Machala: Trends, Challenges, and Opportunities for Brands - Ordoñez Izquierdo, Miguel Alesandro; Feijoo Jaramillo, Irene María; Mite Albán, María Teresa; Viteri Escobar, Carlos Joel; Sarmiento Chugcho, Carlos Bolívar (Revista Universidad de Guayaquil, 2026)
In the specific field of consumer behaviour and sustainable marketing among the millennials population, fashion is often presented as a point of balance that exposes tensions between aesthetics and environmental concern. Above all, many young people, despite expressing sensitivity to these issues, do not necessarily translate that concern into their purchasing decisions. In this scenario, environmental awareness and persuasive campaigns are frequently discussed, yet it is still not entirely clear how perceptions of sustainable fashion, personal motivation and the messages circulating on social media intertwine to truly influence responsible buying. This study focused on 364 university students in Machala and used a structural equation model estimated via partial least squares (PLS-SEM) to follow these relationships jointly. The analyses show that internal motivation and a favourable perception do in fact strengthen environmental judgement, and that exposure to informational content is associated with a greater perceived effectiveness of campaigns. However, what ultimately tips purchase intention is not environmental awareness on its own—its direct effect turned out to be rather modest—but the way the audience interprets the persuasive strength of those campaigns, which ends up operating as the piece that links the messages with purchase motivation. These results suggest that providing information, by itself, falls short: strategies aimed at young audiences need to tap into more personal motives and align with their daily routines for sustainability to start being reflected in everyday consumption choices.